Stagnation Point Flow of CoFe2O4/TiO2-H2O-Casson Nanofluid past a Slippery Stretching/Shrinking Cylindrical Surface in a Darcy–Forchheimer Porous Medium - Kifle Adula Duguma; Oluwole Daniel Makinde; Lemi Guta Enyadene (Journal of Engineering)
Mounting temperatures in electronic devices during operation may damage sensitive internal components if too much thermal energy accumulates inside the system. The advent of an innovative ultrahigh-performance thermal management technology known as nanofluid has provided a veritable platform to improve the system performance and reliability by removing the high heat flux generated in the engineering and industrial devices. This paper examines the combined effects of Darcy–Forchheimer porous medium-resistant heating and viscous dissipation on stagnation point flow of a Casson nanofluid (CoFe2O4-H2O and TiO2-H2O) towards a convectively heated slippery stretching/shrinking cylindrical surface in a porous medium. The governing nonlinear model equations are obtained, analysed, and tackled numerically via the shooting technique with the Runge–Kutta–Fehlberg integration scheme. A unique solution is obtained when the surface is stretching. For shrinking cylindrical surface, the model exhibits nonunique dual solutions for a defined range of parameter values, and a temporal stability analysis is conducted to ascertain the stable and physically achievable solution. The effects of emerging thermophysical parameters on the overall flow structure and thermal management such as velocity and temperature profiles, skin friction, and Nusselt number are quantitatively discussed through graphs and in tabular form. It is found that the thermal performance heat transfer enhancement capability of TiO2-H2O is higher than that of CoFe2O4-H2O. Moreover, the nanofluid thermal performance is enhanced with nanoparticles volume fraction, Casson nanofluid parameter, and Biot number but lessened with porous medium permeability.